Back to work: The effect of a long-term career interruption on subsequent wages in Switzerland - Amélie Speiser (Swiss Journal of Economics and Statistics, 2021)
This paper measures the effect of a long-term career interruption on wages after re-employment. Using data from the Swiss Household Panel (SHP) and a fixed effects estimation method allows us to account for time-constant unobserved heterogeneity. We find a significant wage penalty of about 7% in the first year after re-employment if a worker takes up a job with the same characteristics as the job previously held. This wage penalty finally vanishes after 5 to 6 years. Conducting subsample analyses for men and women, we uncover underlying heterogeneity of the effect. Compared to women, men tend to suffer more from a long-term career interruption, both in terms of a higher wage penalty during the first year of re-employment and a larger subsequent recovery time. Our findings support the assumption that human capital depreciation is not the only reason for wage penalties after re-employment.
Keywords: 330; Career interruption; Re-employment; Wage; Fixed effects; Switzerland